Challenges in the delivery of health services for people living with HIV in Dar es Salaam, Tanzania: a qualitative descriptive study among healthcare providers - Iseselo, Masunga K.; Ambikile, Joel S.; Lukumay, Gift G.; Mosha, Idda H. (Frontiers in Health Services, 2024)
Background Healthcare providers play an important role in the provision of health services in care and treatment clinics (CTCs), as they help clients cope with their HIV/AIDS diseases by providing health education and counseling. Little is known about the challenges that healthcare providers face when providing such services to people living with HIV (PLWH) in low-resource settings. This study aimed to explore and understand the challenges that healthcare providers face in delivering care to PLWH in Dar es Salaam, Tanzania. Materials and methods We conducted a qualitative descriptive study to explore and understand the challenges that healthcare providers face when providing health services to PLWH. This study was carried out in the CTCs in the Ubungo District, Dar es Salaam, Tanzania. A total of 10 healthcare providers were recruited using a purposive sampling technique until information saturation was attained. Face-to-face interviews were conducted to obtain the data. We transcribed the interviews verbatim and analyzed them using reflexive thematic analysis to obtain the themes and subthemes. Findings Client-related challenges included difficulty in managing antiretroviral (ARV) drug reactions of clients and their financial, follow-up, and index tracking problems; facility-related challenges included inadequate and limited space for CTC services, lack of integrated HIV services, and shortage of staff, which needed collaborative efforts to overcome; and healthcare provider-related challenges included a lack of up-to-date knowledge and limited access to health information. These challenges limit the provision of quality HIV care to the clients. Conclusion This study highlights the important challenges that hinder the quality of HIV services at CTCs. The implementation of appropriate infrastructure to promote the privacy and confidentiality of clients is necessary as it alleviates the burden on the jobs of healthcare providers. The findings also suggest that healthcare providers improvise solutions to meet the needs of the clients in the study setting. Permanent resolution is required to overcome the challenges in CTCs. Further research on both providers and clients should be conducted to explore the challenges in CTCs in other similar settings.